DIRECTIONS DE RECHERCHE SUR L’INTERACTION - FLOREA, Ligia Stela (Studia Universitatis Babeș-Bolyai Philosophia, 2022)
Research directions on interaction. This article proposes to consider interaction as a concept and an object of study based on pragmatics and textual linguistics, according to three approaches: discursive genres (Kerbrat-Orecchioni, 1990, 1992), place relationships (Vion, 1992), dialogism and polyphony (Bakhtine, 1970, 1984 and Ducrot, 1980, 1984). These approaches are illustrated by the analysis of several interaction situations: a political debate organised on Romanian television during the 2004 election campaign, two extracts from the literary works Les Parents terribles by Jean Cocteau and La chute by Albert Camus, and a forum in the newspaper Le Figaro (09/2009).